The Implementation of Community-Based Tourism in Paal Beach, North Minahasa Regency - Toar Ezra Kenda; Nyoman Ariana; Anak Agung Putu Agung Suryawan Wiranatha (Cita Konsultindo Research Center, 2024)
Paal Beach is a tourist attraction located in the Likupang Super Priority Destination Area (DSP). Paal Beach itself is one of the tourist attraction that implements community-based tourism. The involvement of the local community at Paal Beach is quite active so that the local community becomes the driver of the tourism industry. This research aims to analyze the implementation of community-based tourism at Paal Beach. This research uses a qualitative method. Data sources will be obtained through observation, interviews and documentation. This research uses the participation ladder from Choguill (1996) and Pretty (1995) to look at the level of local community participation in Paal Beach. In view of the two participation ladders, it can be seen that the level of local community participation meets ladders 1-7 and 1-6. However, the level of local community participation in Paal Beach has not yet reached Empowerment (Choguill) and Self-mobilization (Pretty).